Kategori Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal Bunga Tunggal dan Majemuk - Handayani, Ucik; Hasanah, Rohmatul (Circle: Jurnal Pendidikan Matematika, 2024)
The research was conducted to categorize and describe the creative thinking ability of students of SMK Ma'wattaibin Banjarejo Pagelaran in solving mathematical problems on single flower and compound flower materials. The research involved 13 students of grade X with different abilities in the even semester because according to the material, single flower and compound flower were taught. The research method used was qualitative-descriptive. Written tests and interviews were used for data collection.  Students were given a written test with 2 questions containing indicators of creative thinking skills. The results of the students' answers were analyzed based on indicators of creative thinking ability and then categorized based on the level of creative thinking ability (TKBK). The indicators of creative thinking ability used are fluency, flexibility and novelty. There are five levels of TKBK, including TKBK level 0 (not creative), level 1 (less creative), level 2 (moderately creative), level 3 (creative) and level 4 (very creative). Data analysis techniques include data reduction, data presentation and inference. Triangulation techniques were also used in this study. The results showed that there were 38% students in the uncreative category, 47% students in the less creative category, 15% students in the moderately creative category and no students in the creative and highly creative categories.  Students at the uncreative level cannot fulfill any of the indicators of creative thinking ability. Students in the less creative level can only fulfill the fluency indicator according to their abilities. Students at the moderately creative level can only fulfill the flexibility indicator according to their abilities. Teachers need to train different mathematical problems that have different answers for students. This research is limited to categorizing and describing students' creative thinking skills, as further research can be carried out in relation to strategies to improve students' mathematical creative thinking skills.